2017
DOI: 10.3390/su9111981
|View full text |Cite
|
Sign up to set email alerts
|

Confusion and Misunderstanding—Interpretations and Definitions of Local Food

Abstract: Developing a more resilient food system based on sustainable food production and consumption is of major concern in creating food security. One issue in this complex field concerns the scale of the food system. Trends and tendencies show that the interest for local food has increased the last decade in Sweden, as well as in other parts of the world. Although the concept "local food" is commonly used, research shows that there is no single definition of it, instead definitions and meanings vary widely. This has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 52 publications
1
25
0
4
Order By: Relevance
“…Regional Data included in the table show that the definitions presented in literature and legal acts are fuzzy, which was already emphasized. Also, Granvik et al confirmed that the interpretations and definitions of the term local food might be confusing and may lead to misunderstandings [36].…”
Section: Comparative Criterionmentioning
confidence: 99%
“…Regional Data included in the table show that the definitions presented in literature and legal acts are fuzzy, which was already emphasized. Also, Granvik et al confirmed that the interpretations and definitions of the term local food might be confusing and may lead to misunderstandings [36].…”
Section: Comparative Criterionmentioning
confidence: 99%
“…Local food has also been associated (and sometimes identified) with small-scale or organic production, craftsmanship and the promotion of local food traditions. On a critical note, it should be recognised that some of the aspects associated with local food (such as small scale) do not pertain to it necessarily, since local food may also originate from large food industries (Granvik et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Europe, a growing number of consumers choose local products and associate them with higher quality, healthy eating and environmentally friendly production methods (European Parliament, 2016). Other aspects commonly associated with local food are small-scale production, craftsmanship and promoting local food traditions (Adams & Adams, 2011;Coley et al, 2009;Feenstra, 1997;Granvik et al, 2017;Lang, Stanton & Qu, 2014). Some of the qualities attributed to local food, however, are debatable.…”
Section: Introductionmentioning
confidence: 99%
“…They are sold under different trademarks. Small farmers face a challenge to further improve the safety, health and quality of their products through various innovations that will enable them to maintain and expand their market share [32,33].…”
Section: Theoretical Backgroundmentioning
confidence: 99%